Aproximações entre planejamento estratégico situacional e governança colaborativa: implicações teóricas e práticas - Reis, Jéssica de Oliveira Bottrel (2018)
The dissertation's objective was to identify relations between Strategic Situational Planning (SSP) and Collaborative Governance (CG) and what theoretical and practical implications it generates for public administration, especially in the municipal level. The dissertation is composed by a theoretical article, an article with empirical research and a technical product, and each of them sought a specific objective: a) to relate SSP and CG, pointing out their similarities and divergences; b) to analyze practices and perceptions of managers in municipal governments, confronting them with fundamentals of the SSP and CG; and c) create an booklet to disseminate SSP and CG among public managers. In the first article, similarities were found between the approaches regarding the involvement of non-state actors in public administration, insertion of concern with political factors in management, and focus on problem solving. In the second article, a survey was conducted with questionnaires for managers from Minas Gerais municipalities with more than 20 thousand inhabitants. Surprisingly, a small number of respondents realize that planning at the municipal level is not necessary. It was also possible to identify that concern about governance in public administration is often still seen as negative. It was still possible to observe that managers have difficulties in getting out of the bureaucratic routines to dedicate themselves to more strategic activities, and also that in some cases the focus on the maintenance of power stands out in detriment to the solutions of the society's problems. Concerning the involvement of other social actors in the public administration, it is possible to note the presence of ideas in favor of greater openness of municipal administrations, but such ideas find problems to be practiced, such as the difficulty of citizens' engagement and the difficulty of such actors to adopt a broad view of the issues to be discussed. Finally, an informative booklet was developed about SSP and CG for distribution to the public managers who participated in the research.